Komunikasi Profetik dalam Ruang Publik Digital: Implementasi Ayat-Ayat Komunikasi untuk Kesalehan di Media Sosia - Anisah Indriati (Lisyabab : Jurnal Studi Islam dan Sosial, 2026)
This study aims to explore the application of prophetic communication principles in the digital public sphere, particularly on social media, and to identify how Quranic verses on communication can be applied to enhance piety in digital communication. This study used a qualitative approach, using textual analysis of Quranic verses governing communication principles, as well as interviews with active social media users.The results indicate that principles such as qawlan sadīdan, qawlan karīman, and qawlan layyinan can reduce the spread of hoaxes and hate speech, and improve the quality of interactions on social media. The application of prophetic communication principles can also help create a more ethical, peaceful, and inclusive digital public sphere. However, challenges such as audience diversity and anonymity on social media need to be addressed for these principles to be effectively implemented. This research contributes to the development of Islamic communication theory in the digital context by providing practical insights into the application of Islamic values-based communication principles on social media. The implication of this research is the need for regulations and policies that support the implementation of communication ethics on social media to create a healthier and more respectful digital space.